Increased risk of ventilator‐associated pneumonia in patients after cardiac arrest treated with mild therapeutic hypothermia. Issue 6 (10th April 2022) - Hasslacher, Julia; Steinkohl, Fabian; Ulmer, Hanno; Lehner, Georg; Klein, Sebastian; Mayerhoefer, Timo; Joannidis, Michael
Abstract: Background: We aimed at investigating the incidence, characteristics and outcome of ventilator‐associated pneumonia (VAP) in patients after cardiac arrest (CA) and its potential association with mild therapeutic hypothermia (MTH). We hypothesized, that MTH might increase the risk of VAP. Methods: Prospective observational study including comatose adult patients after successful resuscitation from out‐of‐hospital or in‐hospital CA with presumed cardiac cause admitted to ICU and treated with MTH at 33°C for 24 h or normothermia (NT) with treatment of fever ≥38°C by pharmacological means. The primary outcome measure was the development of VAP. VAP diagnosis included mechanical ventilation >48 h combined with clinical and radiologic criteria. For a microbiologically confirmed VAP (mcVAP), a positive respiratory culture was required. Results: About 23% of 171 patients developed VAP, 6% presented with mcVAP. VAP was associated with increased ICU‐LOS (9 (IQR 5–14) vs. 6 (IQR 3–9) days; p  < .01), ventilator‐dependent days (6 (IQR 4–9) vs. 4 (IQR 2–7) days; p  < .01) and duration of antibiotic treatment (9 (IQR 5–13) vs. 5 (IQR 2–9) days; p  < .01), but not with mortality (OR 0.88 (95% CI: 0.43–1.81); p  = .74). Patients treated with MTH (47%) presented higher VAP (30% vs. 17%; p  = .04) and mcVAP rates (11% vs. 2%; p  = .03). MTH was associated with VAP in multivariable logistic regression analysis with an OR of 2.67 (95% CI: 1.22–5.86); p  = .01. Conclusions: VAP appears to be a common complication in patients after CA, accompanied by more ventilator‐dependent days, prolonged antibiotic treatment, and ICU‐LOS. Treatment with MTH is significantly associated with development of VAP.